ANALISIS FAKTOR – FAKTOR SISTEM INFORMASI MANAJEMEN DI PT. CIMB NIAGA Tbk CABANG BANDUNG - Tri Indra Wijaksana (Institut Informatika Dan Bisnis (IIB) Darmajaya, 2015)
The aim of this research was to find out and study about the influence of management information system in PT. Bank CIMB Niaga Tbk, Bandung branch office which is located at jalan Lembong Bandung. The research method used in this research was ekspanatory survey with research type survey. The test results of 5 indicators of latent variables have a management information system that is effective and consistent reliability so that the variance extracted value meaningful to the information in the latent variable.Keyword: management information system, information system